PENGGUNAAN ASAM TRIIODOBENZOAT PADA BERBAGAI VARIETAS KEDELAI (Glycine max (L.) Merril) - Yunafri Ilham; Aslim Rasyad (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Triiodeobenzoic acid (TIBA) is a plant growth regulator which is expected to synchronize the partition of dry matter translocation into vegetative and to reproductive organs. So that substance may be introduce to greater range of crop cultivation technology to increased yield potential. The objectives of this study are to look at the effect of TIBA application on growth and production of soybean varieties and to identify different response of the varieties to various concentrations of TIBA. A field experiment was conducted by split plot design, where the application of  TIBA 0 ppm, 50 ppm, 100 ppm and 150 ppm as the main plot and three varieties Grobogan, Kaba and Wilis as subplot. Parameters observed were plant height, internode length of the main trunk, date to harvest, number of filled pods per plant, number of seeds per plant, seed weight per plant, harvest index, weight of 100 seeds and yield per m2. The results showed that application of TIBA 50 ppm shortened plant height and internodes length of Kaba and Grobogan. It was shown that application of 100 ppm TIBA could increased yield components and yield per area compared to control indicating the increasing of dry matter translocation to the seed. Keywords: triiodobenzoic acid, soybean varieties, plant height, internodes length, grain yield